Typification of Cotoneaster koidzumii (Maleae, Rosaceae) and two associated names - Jocou, Adriel I. (Phytotaxa, 2020)
The typification of the names Cotoneaster koidzumii, Cotoneaster taitoensis, and Cotoneaster formosanus (Rosaceae) is discussed. Lectotypes are designated for C. koidzumii (Herbarium TI), C. taitoensis (TI), and C. formosanus (TAIF; isolectotypes at PE and TI).